Population-centric counterinsurgency: the conduit for ending Boko Haram insurgency in Nigerias North - Gana, Modu Lawan; Ku Samsu, Ku Hasnita; Ismail, Mohd Mahadee (Diamond Scientific Publication, 2018)
This concept paper analyzed the existing counterinsurgency approaches of Nigeria government in combating an Islamist insurgent Boko Haram in Nigeria. Boko Haram violent armed uprising for the Islamization of Nigeria state in 2009 have cooled bloodily murdered thousands of people and displaced millions of others from their settlements. This has resulted in serious humanitarian situations. To combat the insurgency Nigeria government in collaboration and support of foreign government have adopted numerous counterinsurgency measures. However, despite the consistent counterinsurgency measures, prevailing evidence suggests that the insurgency is far away from being defeated. In contrast, the group sustained its violence attacks unabatedly. Therefore, this paper explored that the sustenance of Boko Haram insurgency in spite of the successive counterinsurgency measures eventuated from the adoption of enemy-centric approach in the combating activities. The paper revealed the repressive military action coupled with draconian laws and policies by the state created public dissension toward the counterinsurgency campaign, therefore, undermine the successes of the campaign. In conclusion, the paper recommends that to effectively tackle the Boko Haram insurgency, Nigeria government need to deviate from the enemy-centric approach and to the population-centric paradigm that should focus on addressing the socioeconomic factors fuelling the insurgent recruitment and support.